Treatment of Recurrent Genotype 1 Hepatitis C Post-Liver Transplantation: Single Center Experience with Telaprevir-Based Triple Therapy - Werner, C. R.; Egetemeyr, D. P.; Nadalin, S.; Königsrainer, A.; Malek, N. P.; Lauer, U. M.; Berg, C. P. (Zeitschrift für Gastroenterologie, 2014)
Recurrent HCV infection post-liver transplantation (post-LT) is still a major challenge in the treatment of hepatitis C virus (HCV) infection. In this retrospective analysis we gathered data about treatment response and safety of all 14 post-LT patients who were treated between 2011 and 2013 at our centre with a telaprevir (TVR)-based triple therapy. Seven out of 14 patients completed the full treatment course of 48 weeks. Five patients achieved a SVR 24, while 3 additional HCV RNA-negative patients are still in follow-up (end of treatment, SVR 12 and 22). Four patients discontinued treatment prematurely due to side effects. A virological non-response at TW 4 was seen in 1 patient. Virological breakthrough was observed in 2 patients at TW 16 and 28, respectively; 1 patient displayed a virological relapse after the end of treatment (EOT). Patients with a complicated course post-LT accumulated most of the severe side effects, largely infections. One patient with cholestatic hepatitis died 11 weeks after discontinuation of treatment due to progressive graft failure. In conclusion, TVR-based triple therapy in post-LT patients reveals an acceptable antiviral efficacy. Unfortunately, severe side effects are frequent and often require therapeutic interventions. Therefore, with the approval of less straining DAA like sofosbuvir in sight, TVR-based triple therapy in post-LT patients should be, if possible avoided.
Keywords: Hepatitis C; Lebertransplantation; SVR; Telaprevir; Nebenwirkungen; cholestatische Rekurrenz der Hepatitis C